Psychological distress among the family members of Intensive Care Unit (ICU) patients: A scoping review - Azura, Abdul Halain; Tang, Li Yoong; Chong, Mei Chan; Noor Airini, Ibrahim; Khatijah Lim, Abdullah * (Wiley, 2022)
Aims and objectives: To map research-based psychological distress among the family members with patients in the intensive care unit (ICU).